Diagnosed with primary adrenal insufficiency? search adrenoleukodystrophy-two brothers presented with similar phenotype - Nur-E-Jannat, Syeda; Ahmed, Dewan Saifuddin (International Journal of Research in Medical Sciences, 2023)
X-linked adrenoleukodystrophy (X-ALD) is a genetic disease with a variety of phenotypic expression. This is the first case report of X-AMN/ALD in two brothers in Bangladesh confirmed by raised VLCFA. Our index patient of 19 years presented on 2014 with adrenal insufficiency, after one year developed progressive spastic paraparesis along with cognitive declination and behavioral abnormality. His only brother was clinically asymptomatic at presentation with Addison’s disease and extensor planter reflexes. After three years of follow up, index patient became bed bound with slurred speech, urinary urge incontinence and his brother developed spastic paraparesis with cognitive impairment. None had gonadal impairment. Follow up MRI after three years revealed lesion in brainstem in both along with atrophy of thoracic segment of spinal cord in index patient and cerebellum, internal capsule involvement in his brother. Both were of pure AMN variety but due to presence of cognitive impairment and behavioral abnormality they can be categorized as cerebral variety of AMN. On 2023, our index patient is still surviving with major functional disability and his brother died on 2019, 5 years of initial diagnosis.